New Challenges in Biorobotics: Incorporating Soft Tissue into Control Systems - Barry A. Trimmer (Applied Bionics and Biomechanics)
The development of truly biomimetic robots requires that soft materials be incorporated into the mechanical design and also used as an integral part of the motor control system. One approach to this challenge is to identify how soft animals control their movements and then apply the found principles in robotic applications. Here I show an example of how a combination of animal kinematics, neural patterning and constitutive modelling of tissues can be used to explore motor control in the caterpillar, Manduca sexta. Although still in the early stages, these findings are being used to design and fabricate a new type of robot that does not have a rigid skeleton and is structured entirely from soft or compliant materials. It is hoped that this new robotic platform will promote the development of actuators, sensors and electronics that are compatible with soft materials.